Leading High Performance School - Christensen, Marshall (Educological discourse, 2014)
In the article creating and maintaining an effective educational system defined as one of the most important responsibilities of every society. Teaching students and leading high performance schools the author considers to be two of the most important callings in life. Much attention is paid to the role of school leaders in the development of educational system.